Biofloc technology (BFT) system improves survival and intestinal health of Carassius auratus larvae subjected to different food management - Besen K.P.* (2023)
© 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.This study evaluated the effect of fish farming under the biofloc system (BFT) and different food managements on zootechnical performance and intestinal health of goldfish (Carassius auratus) larvae. For such, two production systems (clear water and BFT) and three food managements (feed, Artemia and combination of Artemia and feed) were tested on goldfish larviculture through 15 days. The experiment was conducted in a completely randomized 2×3 factorial design with four repetitions. Larvae at early exogenous feeding (0.60±0.01mg) were randomly distributed in conical-bottomed cylindrical containers with 1 L of useful volume at density of 10 larvae L−1. At the end of the experiment, performance and intestinal histomorphometry were evaluated. The BFT system improved survival of goldfish larvae. High ammonia concentrations in the water led to reduced growth of goldfish larvae farmed under the BFT system. Combining Artemia with feed provided a better performance of the goldfish larviculture under the clear water system. For the BFT system, supplementation with feed is apparently not necessary. An increased number of goblet cells on larvae under the BFT system was observed. The BFT system improves survival and intestinal health of goldfish larvae. A reduction in the growth of larvae was observed in the BFT system, possibly associated with an increase in the concentration of toxic ammonia. Inert feed is not recommended as the only food source. Combination of Artemia with inert feed provided better zootechnical performance in goldfish larviculture under the clear water system. For the BFT system, supplementation with feed is apparently not necessary.